System Design Compensation in SMEs XYZ Sector FnB in Bandung City with Comparison Method Adhered and Overlapping - Sembiring, Fernando; Mandy Aileen Lius; Sayid Akmal Bashori; Sendi Setiawan; Sholehatul Mokharomah; Lindawati Kartika (Jurnal Ilmiah Sumber Daya Manusia, 2024)
MSMEs play a role active in increase economy and absorption power work , like increase in GDP for Indonesia. One of form businesses that have potency towards the country is business in the sector culinary . Amount business in the sector culinary increase every years in Bandung City and can give field new job​ for others. Businessman own obligation For arrange structure and scale wages for employee they with consider a number of factor like category , position position , length of service , level education , and abilities . Study This aim For analyze compensation finances received by employees at one of the SMEs in Bandung City will evaluated positions worker the as well as designing structure and scale wages for XYZ SMEs in Bandung City with use Adhered and Overlapping methods . Analysis process use Google Sheets software tool for make it easier calculation and manufacturing graph . Research result show that improvements wages with Adhered method can chosen by SME XYZ because need more spending​ less and more in accordance with expenditure operational from these SMEs